Efficient Adsorption and Removal of Congo Red from Aqueous Solution Using Magnetic Covalent Organic Framework Nanocomposites. Issue 1 (3rd January 2023) - Lu, Sufen; Wei, Yunjiao; Long, Shuixian; Chen, Ziyan; Chen, Feixia; Lin, Haoran; Lu, Junyu
Abstract: In this work, a core‐shell structured magnetic covalent organic framework (Fe3 O4 @TpPDA) was synthesized through simple in‐situ growth method by using 1, 3, 5‐triformylphloroglucinol (Tp) and 1, 4‐phenylenediamine (PDA) as precursors, and used as adsorbents for the efficient adsorption and removal of Congo red from aqueous solution. The as‐prepared Fe3 O4 @TpPDA was characterized by Fourier transform infrared spectroscopy, X‐ray powder diffraction, X‐ray photoelectron spectroscopy spectra and transmission electron microscopy. The influence of initial concentration, adsorption time, and temperature was evaluated. The adsorption of Congo red onto Fe3 O4 @TpPDA was investigated by adsorption models including Langmuir, Freundlich, pseudo‐first‐order and pseudo‐second‐order kinetic models. The adsorption behavior was fitted well with the Langmuir isotherm and consistent with the pseudo secondary dynamics model. The maximum adsorption capacity was found to be 179.4 mg/g. According to thermodynamic analysis, Congo red adsorption is a spontaneous endothermic reaction. Furthermore, the reusability of Fe3 O4 @TpPDA was determined by recycling it up to seven times. Thus, Fe3 O4 @TpPDA was considered to be an excellent adsorbent for the quick and efficient adsorption of Congo red from environmental water. Abstract : The magnetic COF nanocomposite was synthesized via simple in‐situ growth method by using 1, 3, 5‐triformylphloroglucinol (Tp) and 1, 4‐phenylenediamine (PDA) as precursors. The Fe3 O4 @TpPDA shows an excellent adsorbent for the quick and efficient adsorption of Congo red via hydrogen bonding and π‐π interaction.